Dynamic Analysis Of Historical Sultan Hamit Masonry Arch Bridges - Öztürk, Çağrı Onur; Çetın, Senem Yılmaz; Sayın, Erkut (My University, 2023)
There are many historical bridges belonging to various civilizations in our country. Historical bridges also help us understand the sociological, economic and cultural structures of civilizations that lived between the past and the present. Historical bridges have been deformed due to natural events and human factors and some of them have been destroyed. It is extremely important to know the behavior of these bridges against earthquakes, since a large part of our country is located in a region with high earthquake risk. For this reason, the dynamic behavior of structures is examined with numerical and experimental studies, and earthquake analyzes are made using earthquake acceleration records obtained from past earthquakes or artificial earthquakes. In this direction, it is aimed to strengthen the weak aspects of the structures. For this reason, it is necessary to evaluate the behavior of historical masonry bridges that have survived to the present day in order to carry out restoration and protection. In this article, the historical Sultan Hamid I-II and III bridges in the Askale district of Erzurum province are discussed as a numerical application. These bridges were modeled in three dimensions using the SAP2000 finite element program. First of all, static analyzes of the bridges under their own weight were made. Then, the dynamic properties of the bridges were determined by making modal analyzes. After the dynamic properties of the bridges were determined, dynamic analyzes were made in the time period.
Keywords: Macro modelling; linear dynamic analyses; masonory stone bridge